Effect of price and non-price initiatives promotion towards healthy food selection - Masmira Kurniawati, - (Primrose Hall Publishing Group, 2020)
It is the task of marketers to pay attention to the welfare of their consumers. Unfortunately, today's consumer prefers fast food that does not have a balanced nutritional content. As a result, many Indonesians today are overweight. Marketers can influence this purchasing pattern through promotional activities so that consumers will prefer healthy food. Marketers can use various promotional methods to influence consumer purchasing decisions. This study uses priming, price discounts, and behavioural rewards. Utilising an experimental method, this study uses 240 participants. An ANOVA test is used to analyse the data. The analysis shows that consumers would prefer to buy healthy food products provided with a price discount compared to a behavioural reward; there are differences in the consumer response exposed to an ad with text that indicates priming compared to consumers who do not receive priming; and consumers will prefer to buy healthy food after seeing posters containing price promotions compared to priming posters.